Kānsưksā n̄æothāng kānb̨̄orihān kānkhonsong thāng ʻākāt nai ch̄œng phānit : sưksā chaph̨o karanī thāʻākātsayān Phāk N̄ưa t̨̄on bon - Bunrūai Ch̨̄opchai (Phāk Wichā Ratthaprasāsanasāt, Čhulālongk̨̄onmahāwitthayālai, 1992)
Case study on commercial air transportation management in Northern Thailand.